Translating Apȣagana: Conceptual-Affective Modelling as a Tool for Analyzing Historical Indigenous Legal Cultures - Fletcher, Andrew (TTR, 2024)
This paper explores the use of conceptual-affective modelling as a powerful tool for understanding Indigenous and European (or Euro-American) interactions in 18th century colonial North America. It illustrates how dictionaries and lexicons of Indigenous languages compiled by colonial actors, particularly the French Jesuit missionaries, can be harnessed to reveal a previously obscure conceptual world. These linguistic sources have only been used sparingly in the social sciences due to the linguistic and structural difficulties in engaging with what are atypical primary sources. Conceptual-affective modelling permits quantitative and qualitative analyses of the concepts contained within these sources. To demonstrate this, the intersection of Indigenous legal cultures and the Calumet [Apȣagana] has been chosen. First, a study of the Calumet in 17th-century Miami-Illinois–and–French dictionaries is discussed. Compiled in the area known to the French as the Pays des Illinois, these were tools for the evangelization project of the Society of Jesus. Within them are a wealth of words, expressions, and phrases that evoke the reality of the members of the political confederation called the Illinois (though their own term for themselves was Inoca). In a period from which few sources recorded Indigenous voices, these open a window onto language and culture. Second, the challenges of translating concepts pertaining to legal culture between societies with vastly different conceptions of justice are examined. The Calumet is considered in relation to a series of translated speeches by Indigenous leaders made in 1723, connected to a case of homicide. Rather than concentrating on the conflicts that can arise from conceptual divergences, the study investigates how attempts to resolve conflicts between different legal cultures can illuminate the diverse attributes that contribute to meaning and communication.